2020
DOI: 10.3390/ani11010004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hindgut Microbiome of Sheep and Effect of Different Husbandry Conditions

Abstract: The microbiome is now seen as an important resource to understand animal health and welfare in many species. However, there are few studies aiming at identifying the association between fecal microbiome composition and husbandry conditions in sheep. A wide range of stressors associated with management and housing of animals increases the hypothalamic–pituitary axis activity, with growing evidence that the microbiome composition can be modified. Therefore, the purpose of the present study was to describe the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Heat map analysis shows significant differences in the microbiota of the small intestine and large intestine. Comparing the species distribution of LZS group and CK group at the phylum level, it was found that Firmicutes were the most important flora in the intestine, which was also found in other mammals (Chang et al, 2020;Minozzi et al, 2020). Firmicutes is an efficient energy harvesting bacterium, which is closely related to the energy acquisition and immune response regulation of the body.…”
Section: Discussionmentioning
confidence: 90%
“…Heat map analysis shows significant differences in the microbiota of the small intestine and large intestine. Comparing the species distribution of LZS group and CK group at the phylum level, it was found that Firmicutes were the most important flora in the intestine, which was also found in other mammals (Chang et al, 2020;Minozzi et al, 2020). Firmicutes is an efficient energy harvesting bacterium, which is closely related to the energy acquisition and immune response regulation of the body.…”
Section: Discussionmentioning
confidence: 90%
“…This study also discovered that fecal microbial communities in lactating camels of different parities tend to cluster differently. In the gastrointestinal tract samples of yaks, Firmicutes, Bacteroidetes, and Verrucomicrobia were the most abundant phyla [34]. Similarly, in beef cattle, the most common phyla in fecal microbiota included Firmicutes, Bacteroidetes, and Verrucomicrobia [35].…”
Section: Discussionmentioning
confidence: 97%
“…Another recent 16S study compared the microbiome composition in sheep and goats, finding no substantial differences between the two taxa; however, variation did occur depending on age, with older individuals hosting a higher microbial diversity [ 73 ], similar to what has been found in Tibetan sheep [ 71 ]. Interestingly, differences in gut bacterial compositions have been observed among different Chinese sheep breeds from the Tibetan Plateau [ 74 ], contradicting what was found in a similar study on Italian sheep where microbiome differences were mostly due to different husbandry practices [ 75 ]. Like in cattle, however, feed efficiency turned out to be related to a higher abundance and diversity of rumen microbiomes [ 76 ].…”
Section: Microbiome Studies In Livestock Speciesmentioning
confidence: 98%
“…The characterization of the sheep GIT microbiome has revealed its substantial similarity in composition with that of cattle and other ruminants, with Bacteroidetes and Firmicutes making up more than 80 to 90 percent of the gut microbial community [ 67 , 69 ], followed by the phyla Actinobacteria, Proteobacteria, Spirochaetes, and Verrucomicrobia [ 68 , 74 , 82 ]. Bacterioidia and Clostridia are the dominant classes [ 75 ]. Moreover, Bacteroidales and Clostridiales figure among the most abundant orders ( Figure 1 ), while, similar to what is observed in cattle, Eubacteriales and Lactobacillales stand out among Firmicutes.…”
Section: Microbiome Studies In Livestock Speciesmentioning
confidence: 99%
See 1 more Smart Citation